Enhancing science process skills: problem-based learning in salt hydrolysis for metacognition growth - Ratman; Walanda, Daud Karel; Rahmawati, Sitti; Ningsih, Purnama; Ijirana; Prayoga, Ismail; Azzajjad, Muhammad Fath (Journal of Turkish Science Education, 2026)
The demands of today's workforce for knowledge and flexible, cross-disciplinary skills have changed. Through problem-based learning, students can develop the skills necessary for a range of careers. This kind of research employs a pretest-posttest control-group design and is a quasi-experiment. One hundred and twenty-nine students from SMA Negeri 1 South Dampal XI MIPA class made up the study population. Simple random sampling was used to produce the sample. Thirty-two students from class XI MIPA 1 made up the experimental group, while 32 students from class XI MIPA 4 made up the control group. Students using the problem-based learning implementation model exhibited science process abilities with an effect size of 8.92 (M=71.84, SD=7.956), whereas those using the discovery learning model had an effect size of 8.33 (M=72.34, SD=7.872).  For both the problem-based learning implementation model (M = 77.03, SD = 3.961) and the discovery learning model (M = 77.62, SD = 2.738), the effect size value of students’ metacognitive awareness was 5.56. An independent-samples t-test indicated that the difference between the two groups was not statistically significant (t(62) = 0.67, p > 0.05). As a result of the problem-based learning approach, students' science process skills in the salt hydrolysis material improved significantly. Their metacognitive awareness of the material was affected, and there is a positive correlation between students' science process skills and their metacognitive awareness.
Keywords: Problem-based learning; science skills; metacognition growth